Wave packet retrieval by multi-photon quantum beat spectroscopy in helium. (August 2015) - Pazourek, R; Reduzzi, M; Carpeggiani, P A; Sansone, G; Gaarde, M; Schafer, K
Synopsis: We show that we can probe the components of an attosecond bound electron wave packet by mapping the quantum beat signal produced by a synchronized delayed few-cycle infrared pulse into the continuum. In addition, spectrally overlapping peaks that result from one-, two- or three-photon processes from more or less deeply bound states can in principle be interferometrically resolved with high resolution.